Rates of nitrogen and growth retardant trinexapac-ethyl on wheat - Espindula,Marcelo Curitiba (2011)
The objective in this study was to evaluate the effects of nitrogen rates in association with rates of the growth retardant trinexapac-ethyl on wheat. The experiment was conducted in Viçosa, MG and arranged in a 5×4 factorial, randomized block design, with four repetitions. A combination of five nitrogen rates (30, 60, 90, 120 and 150kg ha-1) with four rates of trinexapac-ethyl (0, 62.5, 125 and 187.5g ha-1) were tested. Trinexapac-ethyl promotes reduction of soot dry mass and grain yield at the lowest N rates, but at the highest N rates there is increase in these characteristics. The combination between N and trinexapac-ethyl rates that promotes higher shoot dry mass is 150kg ha-1 and 187g ha-1 but that promotes higher grain yield is 100kg ha-1 and 120g ha-1, respectively.